The urgency of philosophical thought: A review of the foundational concepts of philosophy in human life - Hutama, R. Rofi Adi; Habidah, Nandania; Indriani, Novita (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study discusses the importance of studying philosophy and its significant usefulness in human life. The benefits include enhancing critical reasoning, broadening job opportunities, changing the world, and increasing awareness of various points of view. The research method used was library research. This study aims to explore the basic concept of philosophy in general as a basis or foundation in understanding human life, particularly in the field of education. By studying these basic philosophical concepts, readers will be better equipped to understand the underlying principles of human life and, specifically, the philosophy of education. The results of this study are presented below.